EFFECT OF JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT - Azman ISMAIL,; Mohd Ridwan ABD RAZAK (Management & Marketing)
The purpose of this research is to evaluate the association between job satisfaction and organizational commitment. This research was conducted at Fire and Rescue Department of Malaysia. The findings of this research discovered three significant findings. These are, job satisfaction was significantly associated with organizational commitment, intrinsic satisfaction was significantly associated with organizational commitment, and extrinsic satisfaction was significantly associated with organizational commitment. This findings confirms that when employees satisfied with intrinsic satisfaction and extrinsic satisfaction from his or her job condition may lead to greater organizational commitment in the studied organizations. Further, this research offers discussion, implications and conclusion are presented in the succeeding sections